2020
DOI: 10.1097/aog.0000000000003619
|View full text |Cite
|
Sign up to set email alerts
|

A Quality Improvement Initiative to Increase the Frequency of Vaginal Delivery in Brazilian Hospitals

Abstract: al. A quality improvement initiative to increase the frequency of vaginal delivery in Brazilian hospitals. Obstet Gynecol 2020;135. The authors provided this information as a supplement to their article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(61 citation statements)
references
References 23 publications
2
56
0
Order By: Relevance
“…111,292 women delivered in the period before the hard-stop policy (2008–2010), and 69,742 women delivered after the rollout of the policy (2012–2013). Baseline total CS rate: 26% Baseline early CS rate: 4% Outcomes assessed: CS, maternal morbidity, neonatal morbidity and mortality Borem 2020 [ 37 ] Interrupted time series (ITS) study Study period: 2014 to 2016 Baseline period: January to December 2014 to the year following the set-up period of Projeto Parto Adequado (PPA) or “Appropriate Birth” project; Full implementation period: January to December 2016 Country: Brazil Low risk women (nulliparous, term, singleton, vertex) in Brazilian hospitals. Twenty-eight hospitals enrolled in a 20-month quality improvement (QI) Collaborative that targeted low-risk pregnancies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…111,292 women delivered in the period before the hard-stop policy (2008–2010), and 69,742 women delivered after the rollout of the policy (2012–2013). Baseline total CS rate: 26% Baseline early CS rate: 4% Outcomes assessed: CS, maternal morbidity, neonatal morbidity and mortality Borem 2020 [ 37 ] Interrupted time series (ITS) study Study period: 2014 to 2016 Baseline period: January to December 2014 to the year following the set-up period of Projeto Parto Adequado (PPA) or “Appropriate Birth” project; Full implementation period: January to December 2016 Country: Brazil Low risk women (nulliparous, term, singleton, vertex) in Brazilian hospitals. Twenty-eight hospitals enrolled in a 20-month quality improvement (QI) Collaborative that targeted low-risk pregnancies.…”
Section: Resultsmentioning
confidence: 99%
“…The study found no effect on elective CS (OR 1.00, 95% CI 0.97 to 1.03). An additional study (Brazil) [37] assessed the effect of a multifaceted quality improvement initiative ("Appropriate Birth"), that among other change packages, included new contracts between payers and providers and between health plan and hospital creating incentives for quality and safety. Vaginal births increased following implementation of the quality improvement initiative (relative increase of 1.62, 95% CI 1.27 to 2.07).…”
Section: Other Interventionsmentioning
confidence: 99%
“…The PPA is a quality improvement project of childbirth care implemented in Brazilian public and private hospitals, with the goal of increasing the percentage of vaginal deliveries and reducing the rate of hospitalization in a neonatal intensive care unit (NICU) [11][12][13] . It is an ongoing project, started in May 2015 and developed in three phases described in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In the rst phase of the project, managers and local leaders participated in ve face-to-face learning sessions in addition to monthly virtual learning sessions, focusing on training in the improvement model, initial tests of change to reduce the cesarean rate based on the four PPA components and sharing successful experiences and challenges in implementing changes. In addition, the project offered clinical training at realistic simulation centers, with a focus on assisting physiological vaginal delivery and managing obstetric complications 12 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation